2020
DOI: 10.1101/2020.11.05.370080
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective co-activation of α7- and α4β2-nicotinic acetylcholine receptors reverses beta-amyloid-induced synaptic dysfunction

Abstract: Beta-amyloid (Aβ) has been recognized as an early trigger in the pathogenesis of Alzheimers disease (AD) leading to synaptic and cognitive impairments. Aβ can alter neuronal signaling through interactions with nicotinic acetylcholine receptors (nAChRs), contributing to synaptic dysfunction in AD. The three major nAChR subtypes in the hippocampus are composed of α7-, α4β2-, and α3β4-nAChRs. A selectively affects α7- and α4β2-nAChRs, but not α3β4-nAChRs in hippocampal neurons, resulting inneuronal hyperexcitatio… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 90 publications
4
15
0
Order By: Relevance
“…To identify the binding site for Aβ42, we performed the exhaustive scan of the whole extracellular receptor domain using ClusPro. The best-scoring poses (8/10) converged to the site, which partially overlaps with the reported α-BTX binding sites, consistent with the reports on α7 receptor activation via orthosteric modality reversing the Aβ42 binding (Roberts et al, 2021). Therefore, we concluded that the amyloid β (Aβ42) binding site overlaps with that for α-BTX.…”
Section: The Effect Of Dupα7 Subunits On Macromolecular Ligand Bindingsupporting
confidence: 87%
See 2 more Smart Citations
“…To identify the binding site for Aβ42, we performed the exhaustive scan of the whole extracellular receptor domain using ClusPro. The best-scoring poses (8/10) converged to the site, which partially overlaps with the reported α-BTX binding sites, consistent with the reports on α7 receptor activation via orthosteric modality reversing the Aβ42 binding (Roberts et al, 2021). Therefore, we concluded that the amyloid β (Aβ42) binding site overlaps with that for α-BTX.…”
Section: The Effect Of Dupα7 Subunits On Macromolecular Ligand Bindingsupporting
confidence: 87%
“…For Aβ42 interactions, the ligand residues that interacted with the receptor binding sites were located in the C-terminal regions of the Aβ42 monomer ( Table 2). The predicted binding affinity of the Aβ42 to the binding site comprising two α7 subunits (the canonical receptor) was in the low nM range, consistent with available experimental data (Roberts et al, 2021). As a comparison, α-BTX was predicted to bind to the canonical a7 binding sites with one order of magnitude lower (high pM range) than Aβ.…”
Section: The Effect Of Dupα7 Subunits On Macromolecular Ligand Bindingsupporting
confidence: 78%
See 1 more Smart Citation
“…While the experimental structure of α-BTX-α7 is known (PDB code: 4HQP), the structural information on interactions between receptors containing Dupα7 subunits and α-BTX is missing. Aβ 42 and α7 interact with high affinity [ 19 , 20 ]. However, the details of those interactions remain elusive.…”
Section: Resultsmentioning
confidence: 99%
“…Aβ damages nAChRs, and in particular α7 nAChR, directly, thereby altering neuronal signaling and contributing to the synaptic dysfunction associated with AD. Computational modeling indicates that arginine-208 and glutamate-211 in α7 nAChR are involved in their interaction with Aβ [65].…”
Section: Discussionmentioning
confidence: 99%